2017
DOI: 10.1177/2325967117703398
|View full text |Cite
|
Sign up to set email alerts
|

The Coracoacromial Ligament: Anatomy, Function, and Clinical Significance

Abstract: The coracoacromial ligament (CAL) was first described as a pain generator by Dr Charles Neer in the early 1970s. Since that time, considerable controversy regarding CAL management during acromioplasty has persisted. This review aims to better understand the role of the CAL in shoulder physiology and pathology. Sixty-six articles from 1958 to 2016 were identified using an electronic search of PubMed, Cochrane Library, AccessMedicine, and MD Consult for case series as well as cohort and prospective studies. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 61 publications
(141 reference statements)
1
25
1
1
Order By: Relevance
“…Then, several studies stated the potential disadvantages of the CAL resection, involving muscle weakness, adhesive capsulitis in the acromial space that limited shoulder mobility, and anterosuperior glenohumeral instability [ 31 33 ]. Rothenberg et al[ 34 ] found the CAL played an important role in mechanosensory feedback loops that helped to dynamically stabilize the entire range of motion of the shoulder. Cay et al[ 35 ] examined 40 patients undergoing rotator cuff repairs via magnetic resonance imaging and found that the acromio-humeral and coraco-humeral distances were narrower than normal limits in patients with rotator cuff tears.…”
Section: Discussionmentioning
confidence: 99%
“…Then, several studies stated the potential disadvantages of the CAL resection, involving muscle weakness, adhesive capsulitis in the acromial space that limited shoulder mobility, and anterosuperior glenohumeral instability [ 31 33 ]. Rothenberg et al[ 34 ] found the CAL played an important role in mechanosensory feedback loops that helped to dynamically stabilize the entire range of motion of the shoulder. Cay et al[ 35 ] examined 40 patients undergoing rotator cuff repairs via magnetic resonance imaging and found that the acromio-humeral and coraco-humeral distances were narrower than normal limits in patients with rotator cuff tears.…”
Section: Discussionmentioning
confidence: 99%
“…The exact role of CAL is still not clear and is debated in the literature. The ligament's own mechanoreceptors and deformation of the ligament on dynamic ultrasound scan are reported, which suggests its function as a restraint and also with a role in proprioception [22] . It is also reported the ligament can reform or regenerate after surgical transection, suggesting its functional importance as an anatomical structure [23][24] .…”
Section: Graphmentioning
confidence: 93%
“…The coracoacromial ligament (CAL) connects two different parts of the scapula: the coracoid process and the acromion (Figure 7 ). It extends from the inferior anterolateral surface of the acromion to insert onto the lateral edge of the coracoid process [ 24 ]. The CAL forms the coracoacromial arch, which serves several anatomical purposes.…”
Section: Reviewmentioning
confidence: 99%
“…When ossified or calcified, the CAL can contribute to shoulder impingement syndrome (SIS), which occurs as a result of repetitive contact between the coracoacromial arch and rotator cuff muscles, leading to inflammation [ 24 ]. According to Kijima, et al, as the CAL becomes stiffer and more ossified, the pressure exerted by contact between the rotator cuff and the coracoacromial arch increases, aggravating the condition [ 25 ].…”
Section: Reviewmentioning
confidence: 99%